The Shapeshifting and Boundary Crossings of Socially Engaged Art - Bourgault, Rebecca (Art/Research International, 2022)
Socially engaged art practices are understood to borrow from and overlap with several disciplinary territories, crossing over into contexts that, in the process of engaging in civic work and everyday actions, obscure their identity as art and aesthetic practices. The article examines the complications that result from co-existing in various ontological sets of properties, through the presentation of a socially engaged project rooted simultaneously in art, social work, education, and ethnography, and where the author acts and performs as an artist, scholar, and facilitator. Participants in the project embody multiple identities which are dependent on changing perspectives and conditions. Arguing for a relevant ethical orientation to research adapted to the transdisciplinary positions of such community-based projects, the inquiry further interrogates the wrangle between the expectations that symbolic capital is typically accrued to artists engaged in these practices and the inconspicuous agency of quiet activism that offers potent alternative forms of resistance.